Implementation Status and Challenges of Pharmacovigilance Program in Ethiopia: A Mixed-Methods Study - Sisay Endale Biru MSc; Tesfa Marew Wallelign MSc; Teferi Gedif Fenta PhD (SAGE Publishing, 2024)
Functional pharmacovigilance systems are vital to ensure patient safety. There is a paucity of information on the organizational functionality of pharmacovigilance program in Ethiopia. This study assessed the pharmacovigilance programs and its implementation status in Ethiopia. A mixed study design was employed to assess pharmacovigilance functionality in hospitals, pharmaceutical companies, and the National Regulatory Authority. World Health Organization's Pharmacovigilance Indicators and Key Informant Interview Guide were used for data collection. Quantitative data were analyzed using Microsoft Excel (2013), while thematic analysis was used for qualitative study. Of the 30 hospitals covered, only one had a Pharmacovigilance Unit with a dedicated budget, three (10%) had assigned staff, and seven (23.3%) had implemented Standard Operating Procedures. Similarly, 4 (12.5%) of the 32 pharmaceutical companies had separate pharmacovigilance divisions, 12 (37.5%) had a regulatory affairs unit, and 5 (15.6%) had a pharmacovigilance budget. The National Pharmacovigilance Center has the most structure, process, and pharmacovigilance practices. Resource constraints and a weak reporting system were identified as major challenges, while patient harm, loss of confidence, increased circulation of unsafe products, and economic costs were reported as consequences. Increasing training, engaging stakeholders, and improving the regulatory system were recommended as key interventional strategies. Most hospitals and pharmaceutical companies lack most of pharmacovigilance system indicators. However, the national regulatory authority fulfilled most of the elements of Pharmacovigilance systems.